A rare mimic of cecal neoplasia - Albrecht, Thomas; Frankenberg, Moritz von; Goeppert, Benjamin (Clinical Case Reports, 2021)
Appendiceal intussusception is a rare, but relevant differential diagnosis of colorectal neoplasia on endoscopy. Misdiagnosis as polyp and endoscopic removal may result in severe iatrogenic complications.